Surgical approaches to maintaining sinus rhythm in patients with type 2 diabetes and long-term persistent atrial fibrillation - I. A. Khamnagadaev; A. S. Zotov; O. O. Shelest; I. A. Bulavina; A. A. Glupak; Z. A. Zotova; E. R. Sakharov; I. Z. Bondarenko; O. A. Shatskaya; R. I. Habazov; A. V. Troitsky; N. G. Mokrysheva (Сахарный диабет)
BACKGROUND: Treatment of patients with diabetes mellitus (DM) and a long-term persistent form of atrial fibrillation (AF) is an unsolved problem of the healthcare system due to a high risk of disability and mortality. Considering low effectiveness of drug treatment for AF, surgical technologies have been introduced into clinical practice in most countries, but their effectiveness has not been validated for patients with DM. According to various researches isolated interventional treatment of patients with AF and DM is associated with a high rate of recurrence compared to patients without disorders of carbohydrate metabolism. The feasibility of using other surgical approaches (the isolated thoracoscopic procedure or the isolated thoracoscopic procedure in combination with intracardiac intervention) for the treatment of AF for patients with DM has not been determined yet.AIM: To evaluate the effectiveness and safety of a staged surgical approach to release patients with DM from AF.MATERIALS AND METHODS: The study included 19 patients aged 53–73 with DM and long persistent AF. Among them there were 4 (21,4%) women and 15 (78,9%) men. To maintain sinus rhythm all patients were undergone with thoracoscopic epicardial ablation. In three mounts, later the invasive electrophysiological studies and radiofrequency ablation were carried out due to reconnection of left atrium (LA).RESULTS: At the end of the blinded period sinus rhythm was maintained for 17 (89,5%) patients during the observation period. Two patients (10.5%) had AF recurrence. In both cases, the second stage of treatment wasperformed (electrophysiology study and endocardial ablation). Amid normal sinus rhythm after thoracoscopic epicardial ablation the volume of the LA (p=0,013) and the N-terminal prohormone of brain natriuretic peptide (NT-proBNP) (p=0,014) significant decreased. No adverse events were recorded in the perioperative or long-term periods.CONCLUSION: Аccording to our pilot study, the staged approach to surgical maintenance of sinus rhythm for patients with diabetes and persistent form of atrial fibrillation can be an optimal strategy. The endocardial stage could be performed for this category of patients in case of recurrence of tachysystolic cardiac arrhythmias.